Exploration of the minimum necessary FVIII level at different physical activity levels in pediatric patients with hemophilia A - Ai, Di; Huang, Kun; Li, Gang; Zhen, Yingzi; Wu, Xinyi; Zhang, Ningning; Huo, Aihua; Chen, Zhenping; Wu, Runhui (Frontiers in Pediatrics, 2022)
Background Physical activity can increase joint stability and reduce the risk of injury in hemophilia patients. There is limited clinical data on target trough FVIII levels during physical activity in hemophilia A patients. Hence, this study aimed to explore the target trough FVIII level required to avoid bleeding during different physical activities in hemophilia A patients. Methods Patients with severe or moderate hemophilia A, who underwent pharmacokinetics (PK) tests at our center were enrolled in this study. Physical activities and clinical information such as bleeding were recorded. The FVIII level during physical activity was calculated by the WAPPS-Hemo. Results A total of 105 patients were enrolled in this study. A total of 373 physical activities were recorded, of which 57.6% (215/373) was low-risk activities and the remaining 42.4% (158/373) was medium-risk activities. Most common physical activities were bicycling (59.0%), swimming (43.8%), running (48.6%), and jumping rope (41.0%). The FVIII trough level of low-risk physical activity was 3.8 IU/dl (AUC = 0.781, p = 0.002) and moderate-risk physical activity was 7.7 IU/dl (AUC = 0.809, p < 0.001). FVIII trough levels [low-risk activities: 6.1 (3.1, 13.2) IU/dl vs. 7.7 (2.3, 10.5) IU/dl, moderate-risk activities: 9.6 (5.8, 16.9) IU/dl vs. 10.2 (5.5, 11.0) IU/dl] were not statistically different between the mild arthropathy group and the moderate-severe arthropathy group. Multiple bleeding risk tended to increase with physical activities classified as moderate-risk (OR [95% CI]: 3.815 [1.766–8.238], p = 0.001). Conclusion The minimum necessary FVIII level increased with higher risk physical activity, irrespective of arthropathy.